Análise Econômica-Ecológica: Agroecologia e Sistemas Agroflorestais Sucessionais na Serra dos Tapes (RS) - Santin, Fátima Giovana Tessmer (2023)
The current hegemonic model of agricultural production comes from the Green Revolution and advocates an industrial agriculture that has proven to be ecologically unsustainable. Several movements oppose this model, such as Agroecology and Ecological Economics. Within these counter-hegemonic movements there is a specific interest in successional agroforestry systems. Under this approach, the objective of this research is to evaluate the economic-ecological impacts of Successional Agroforestry Systems (SAFS) on agroecosystems in Serra dos Tapes (RS). For this, was used the method LUME: Ecological-Economic Assessment of Agroecosystems developed by Assessoria e Serviços a Projetos em Agricultura Alternativa (AS-PTA) based on its accumulated experiences ince 1989. This method provides a theoretical-methodological and analytical apparatus of a mixed model (quali-quantitative). With this tool, three agroecosystems located in Serra dos Tapes (RS) that have been producing in SAFS for over 10 years were studied. Among the main results, the SAFS have positive economic and ecological impacts on the Serra dos Tapes agroecosystems, are low cost, generate monetary income with productive diversity, produce their own inputs, the work itself is what adds value, and this production integrates the food of the agroecosystems themselves. With this, it is concluded that this production model provides high productive diversity and increased biodiversity in the place, in addition to being related to self-consumption and fostering territorial markets, proving to be a relevant tool for the reproduction of agroecological family farming.